Pusat Pelatihan Selam di Kabupaten Kepulauan Selayar - Maghfirayanti, Nur; Lukman, Muhammad Yusri; said, Juhana (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
One of the marine tourism trends that is starting to develop in Indonesia is diving tourism, which known as "diving". Seeing from the potential for marine tourism in various regions, there is Selayar Islands Regency which is one of the areas in Indonesia that has abundant underwater natural resources and has dozens of diving spots. It is undeniable that diving tourism, which is increasingly popular, opens economic taps for the surrounding community but also poses ecological challenges. This is because not all visitors are equipped with basic knowledge about how to treat marine life and coral reefs. Therefore educational facilities are needed in the realm of diving tourism to increase the knowledge and awareness of tourists which function as a means of diving training for visitors. Training facilities or dive centers are expected to be able to support tourism so that this dive center is intended to improve the quality of tourism and the sustainability of underwater ecosystems. The dive center in Selayar Islands Regency is planned using a Tropical Architecture concept approach so that later the building is expected to be able to adapt according to the local climate with its functions and characteristics.